PROGRAM AGROPOLITAN BERBASIS JAGUNG DAN KONDISI EKONOMI PETANI JAGUNG - Mochammad Sakir (LP2M Universitas Bina Mandiri Gorontalo, 2018)
The purpose of this study was to explain and analyze the contribution of -based program on to economic condition of maize farmers in Kabupaten Gorontalo, Kabupaten Boalemo, dan Kabupaten Pohuwato Gorontalo Province. The maize-based agropolitan program was a policy of the Gorontalo Provincial Government which was an integrated approach to rural development, especially maize farming. The economic conditions of farmers. In this study are into the area of ​​land ownership, the production of maize in one season, and the income of the farmers. This study employed survey design fro quantitative approach. Data collection using questionnaires through interviews with farmers. The results were analyzed by using t-test to test economic condition of farmers from 2007 to 2017. While the respondent in this research was maize farmer land owners participant of the program, during from 2007 until 2017. The study found that the maize-based agropolitan program in Kabupaten Gorontalo, Kabupaten Boalemo, dan Kabupaten Pohuwato Gorontalo Province had an impact on the economic condition of maize farmers. The result of the increased of land ownership, maize production and income